Evolving expectations around early management of multiple sclerosis - Gold, Ralf (SAGE Publications, 2010)
Multiple sclerosis is a progressive inflammatory disease of the central nervous system. With prevention or at least delay of disease progression as a key target in the management of multiple sclerosis, current opinion on treatment encourages early intervention with well-tolerated disease-modifying treatments in order to optimize long-term clinical outcomes. Patients presenting with a clinically isolated syndrome (CIS) may progress to clinically definite multiple sclerosis, and clinical trials have demonstrated that early treatment with interferon beta can reduce the conversion rate. Cognitive impairment may already be present in patients with CISs. Today there is evolving evidence that cognitive impairment may be relevant for prognosis and that early treatment with interferon beta may also have a protective effect on the cognitive function. As an accumulation of neuronal loss is now considered to underlie the development of persistent disability in multiple sclerosis, it is crucial that treatment can protect against neuronal damage. In addition to its anti-inflammatory activity, interferon beta may have direct and indirect neuroprotective effects, and several studies have explored the role of interferon beta in regulating neuroprotective factors. With over 15 years of clinical experience as evidence, the long-term safety and efficacy of interferon beta treatment is unquestionable. Results from the CIS studies have demonstrated the high percentage of patients converting to clinically definite multiple sclerosis without treatment and the short- and long-term benefits of an early use of disease-modifying treatments. These findings support starting disease-modifying treatment as soon as the diagnosis of MS is reasonably formulated.